EFFECTS OF PRENYLATED ISOFLAVONES OSAJIN AND POMIFERIN IN PREMEDICATION ON HEART ISCHEMIA-REPERFUSION - Florian, Tomas; Necas, Jiri; Bartosikova, Lenka; Klusakova, Jarmila; Suchy, Vaclav; El Naggar, ElMoataz B.; Janostikova, Eva; Bartosik, Tomas (Biomedical papers, 2006)
The present 15 days study was undertaken to evaluate the cardioprotective potential of the prenylated isoflavones osajin and pomiferin isolated from the infructences of Maclura pomifera, Moraceae, against ischemia-reperfusion induced injury in rat hearts as a model of antioxidant-based composite therapy. The study was performed on isolated, modified Langendorff-perfused rat hearts and the ischemia of heart was induced by stopping coronary flow for 30 min followed by 60 min of reperfusion (14 ml min-1). The Wistar rats were divided into four groups. The first treatment group received osajin (5 mg/kg/day in 0.5% Avicel); the second treatment group received pomiferin (5 mg/kg/day in 0.5% Avicel); the placebo group received only 0.5 Avicel; the last was an untreated control group. Biochemical indicator of oxidative damage-lipid peroxidation product malondialdehyde, antioxidant enzymes - superoxide dismutase, glutathione peroxidase, total antioxidant activity in serum and myocardium were evaluated. The effect of osajin and pomiferin on cardiac function, left ventricular end-diastolic pressure, left ventricular pressure and peak positive +dP/dt ischemia and reperfusion, also was examined. The results demonstrate that osajin and pomiferin attenuates the myocardial dysfunction provoked by ischemiareperfusion. This was confirmed by an increase in both antioxidant enzyme values and total antioxidant activity. The cardioprotection provided by osajin and pomiferin treatment results from the suppression of oxidative stress and this correlates with improved ventricular function.
Keywords: Maclura pomifera/Isoflavones osajin and pomiferin/Heart ischemia-reperfusion/ Free oxygen radicals